Structural and Karst Studies Using 3D Digital Outcrop Model: A Case Study in Gunung Keriang, Kedah, Peninsular Malaysia - Eng, Tan Yan; Meng, Choong Chee; Aznan, Muhammad Amzar Bin; Rosni, Amirruddin Bin; Yusof, Muhammad Aslam MD; Mohamed, Muhammad Azfar Bin; A.B. Rahman, Siti Sarah Binti (Indonesian Journal on Geoscience, 2024)
A digital outcrop model (DOM) of the Permo-Triassic limestone of Gunung Keriang, Kedah, was constructed for structural analysis and karst study. Structural analysis of beddings and fractures within the DOM revealed that the limestone beds are characterized by gently inclined planes with NE ̶ SW and NW ̶ SE strikes, forming an upright N ̶ S trending synclinal fold, and being cross-cut by four steeply-dipping fracture sets (NE ̶ SW, NW ̶ SE, N ̶ S, and E ̶ W). The synthesis of these fracture sets indicates that the NW ̶ SE and NE ̶ SW fractures form a conjugate pattern suggestive of E ̶ W shortening, which aligns with the observed N ̶ S fold. Karst development, including elongated sinkholes and cave paths oriented in the NE ̶ SW direction, correlates with the fracture patterns, highlighting the NE ̶SW fracture network significant role in karst formation. The integrated data supports the hypothesis that these fracture patterns are major factors in the dissolution and development of karst features in the region.